Cake Paradise Boutique / Siti Farhanah Madi... [et al.] - Said, Shatreena; Norbin, Nurasyikin; Ismail, Nursaleha; Osman, Nur Farihin; Madi, Siti Farhanah (2013)
The name of our company is Cake Paradise Boutique, The name of this company are formed according to our business oriented which are wholly cakes making which it has the various unique designs and shape. The cake Boutique Paradise are partnership business oriented. Thus, the business is focusing on every level of people wheatear for a local people or from outsider. Cake Paradise Boutique exists in order to make all people to enjoy the taste of various cakes which can be afforded at cheaper price. The idea in making this cakes business came from our observation through the cakes shops all over the area in Sulaman, that we are convinced that the price is expensive. Through the observation, we will make people lives better and happy by giving them a special service on cakes making for any days or any occasion. The location for our business is at lborneo Hypermall in Sulaman. The reason behind us choosing this location is because there are many people from all walks of life, therefore a high target markets.